Antecedents of Firm’s Risk-play – A Structural Equation Modeling Approach in an Emerging Market Context - Ranjan Dasgupta; Rashmi Singh (Australasian Accounting, Business and Finance Journal, 2021)
Firm-risk and managerial risk-taking though distinct are used interchangeably in empirical literature. Here, we identify these two distinctly by examining different proxies for them. We use income stream uncertainty and accounting beta to proxy firm-risk, and market risk and capital intensity ratio represent managerial risk-taking. Once defined, our objective is to find the antecedents of both these by using the most advanced structural equation modelling (SEM) approach from created constructs of performance, psychological, corporate governance, shareholding patterns, fundamental valuation and firm’s characteristics drivers. We formulate seven hypotheses based on empirical literature representing these constructs. We use data of 269 Indian firms for 18 (1999-2017) years to run SEM and then analyse our results individually and combinedly. SEM is used here to test the unidimensionality of the seven constructs (consisting of 19 drivers) and to analyze these drivers (i.e. antecedents) influence on firm-risk and managerial risk-taking i.e. firm’s risk-play. Results prove that present firm-performance, corporate governance drivers, promoters’ shareholding and firm’s characteristics are driving firm’s risk-play. However, fundamental valuation drivers have no role to play in influencing income stream uncertainty, systematic operating risks and managerial risk-attitudes. Psychological drivers and foreign shareholdings act only as a catalyst of firm-risk.
Keywords: Firm-risk drivers; Managerial risk-taking drivers; Corporate governance; Shareholdings; Firm characteristics; Structural equation modelling